Case study: Mokti’s Ice Cream / Nur Amirah Ismail … [et al.] - Ismail, Nur Amirah; Mohammad, Nurul Izzatie; Ismail, Nur Alesya; Binti Awang Kechil, Siti Munirah; Baharin, Anis Sofiya (2022)
Mokti's business was studied in this case study to analyze the company's business, which included organization structure, product and services, business, marketing and operation strategy, and financial achievement. In addition, this case study focuses on the business model canvas, which includes customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partners, cost structure, and finally findings and discussions. In terms of products and services, we can conclude that Mokti manufactures ice cream, including soft serving ice cream, popsicles and tubs, as well as coffee. In terms of business strategy, we are focusing on identifying opportunities as well as developing additional channels for growth. Mokti's marketing strategies include product strategy, pricing strategy, distribution strategy, and promotion strategy. Following that, Mokti's ice cream ensures that quality checks are performed, that experience is improved, and that production planning is included in the operation strategy. In terms of financial success, Mokti's ice cream has gained 85 outlets both locally and internationally, from Perlis to Istanbul. Following that, we can confirm that Mokti's ice cream customer segments are teenagers, dessert lovers, students, and mass customers, based on our research. Mokti's ice cream uses retailers, outlets, franchises, and main factories as channels in their business. Mokti's ice cream's key resources are ingredients, brand, company employees, branch of locations, financial resources, physical resources, and human resources. Mokti's ice cream's key partners include gula apong, famous amos, boba, ice cream packaging, honeycomb, cornflakes, foodpanda, grabfood, qr pay, and paypal. Foodpanda and GrabFood will make delivery services more convenient for customers. Mokti is also concerned with their value propositions, which include low product prices, a wide range of flavours, and consistent distribution across the country, from Perlis to Istanbul. Mokti's earn money from customers who walk into stores, social media, and other sources in order to provide good services and ensure that customers are satisfied with their purchases. The cost structure includes marketing costs, employee salaries, ingredients, store and facility construction costs to be paid annually or monthly.